Panoptic Missorts and the Hegemony of U.S. Data Privacy Policy - Blevins, Jeffrey Layne (The Political Economy of Communication, 2017)
The amount and scope of data mining practices from our online activities and personal digital media devices should yield highly detailed profiles of our individual preferences, so that marketers can create decidedly calculated and targeted advertising messages.Â  Oscar Gandy described an early version of this process in his 1993 book, The Panoptic Sort: A Political Economy of Personal Information, and critiqued some of its ill effects.Â  This analysis reexamines Gandy's critique and explores further concerns about the panoptic machine, including the 'missort' of personal information and the misrepresentation of individuals. This political economic analysis shows the inability of U.S. privacy policy to properly address the harms of missorting, and examines the hegemonic nature of 'big data' ownership and control.